Scale-up of micro- and milli-reactors: An overview of strategies, design principles and applications. (May 2021) - Dong, Zhengya; Wen, Zhenghui; Zhao, Fang; Kuhn, Simon; Noël, Timothy
Abstract: Continuous-flow microreactor technology has been embraced by researchers in academia and industry due to its excellent transport properties and the increased safety and control over challenging chemical transformations. Despite its popularity, scaling the benefits associated with the microenvironment has proven to be a daunting challenge. This review provides an up-to-date overview concerning the different scale-up approaches of micro/milli-reactors, including numbering up (both internal and external), sizing up (increasing length, geometry similarity and constant pressure drop strategies) and a combination of numbering up and sizing up. The strategies, design principles and applications of each approach have been discussed in detail. Each scale-up approach has its merits and limitations. However, scale-up factors, that are required in the fine chemical and pharmaceutical industry, are within reach when different scale-up approaches are combined.